ASEAN+3 bond market guide 2018 Vietnam. (ASEAN+3 bond market guides., 2018)
The ASEAN+3 Bond Market Guide 2018: Viet Nam is an outcome of the strong support and kind contributions of ASEAN+3 Bond Market Forum members and experts, particularly those from the country. It is part of the ASEAN+3 Bond Market Guide series comprising a comprehensive explanation of the region bond markets. The series provides relevant information such as the history, legal and regulatory framework, specific characteristics, and trading and transaction (including settlement systems) trends of markets in the region.